Dispersion of InPZnS/ZnSe/ZnS multishell quantum dots (QDs) in water: extension to QDs with different core sizes and identical shell thickness. Issue 5 (19th February 2021) - Heyne, Benjamin; Geßner, André; Wedel, Armin; Taubert, Andreas
Abstract: We have previously shown (Nanomaterials, 2020, 10 (9), 1858) that InPZnS/ZnSe/ZnS multishell quantum dots (QDs) with a variety of shell thicknesses can be dispersed in water using a ligand exchange reaction with mercaptocarboxylic acids. Here, we demonstrate that the concept can further be extended to a larger variety of QD core sizes while keeping the shell thickness constant. The photoluminescence quantum yield of the QDs in the aqueous phase depends on the QD size and the QDs only show a slight red‐shift upon dispersion in water. This provides access to a larger group of particles with different emission colors, which is interesting for application in e. g. biological or medical diagnostics. Abstract :